Strategi Pengembangan Industri Kecil Pembuatan Gula Kelapa - Agustianis, Ayu; Simatupang, David Oscar; Widiastuti, Maria Maghdalena Diana (Musamus University, 2020)
This study aims to identify internal (strengths and weaknesses) and external (opportunities and threats). The method used is the SWOT analysis technique and qualitative descriptive. The research was conducted in Kumbe Village, Malind District, Merauke Regency in April - May 2018. The results of the identification of IFAS and EFAS show that strengths consist of: availability of raw materials (sap), does not require high technology, equipment that is easily available, low capital, demand market, and the profits earned. Weaknesses consist of: labor availability, workforce expertise, business management, seasons affecting production. Opportunities consist of: market opportunities, customary law support, business permits from the government, village economic development for the existence of coconut sugar businesses, the superiority of local coconut sugar quality over competing coconut sugar. Threats consist of: lack of socialization, training and motivation from the government, lack of input for production inputs, monitoring of coconut sugar prices from the government, low coconut sugar prices, certification of coconut sugar commodities.